Mix-mode fracture of microplates - Cong, Pham Hong; Thom, Do Van; Duc, Doan Hong; Minh, Phung Van; Nhat, Pham Duc; Truong, Dong Xuan (Vietnam Journal of Science and Technology, 2024)
This paper studies the crack propagation of microplates in mix-mode based on a modified couple stress theory (MCST) and the phase-field method. Compared to the stress couple hypothesis, the MCST contains many novel aspects, most notably the symmetry of the couple stress tensor and the involvement of a single internal length scale parameter. These features make the modified couple stress theory easier to use. The formulas are established based on the finite element method (FEM). When calculated using the MCST versus classical theory (regardless of size effect), the calculation results unmistakably demonstrate the differences in the mechanical characteristics of the system during the crack development. The difference is demonstrated by specific examples, with clear explanations and many physical meanings. This work will be helpful for researchers studying the process of microstructural fracture formation.